Documentary Making for Digital Humanists. - Reid, Darren R.; Sanders, Brett (Cambridge, UK : Open Book Publishers, 2021)
This fluent and comprehensive field guide responds to increased interest, across the humanities, in the ways in which digital technologies can disrupt and open up new research and pedagogical avenues. It is designed to help scholars and students engage with their subjects using an audio-visual grammar, and to allow readers to efficiently gain the technical and theoretical skills necessary to create and disseminate their own trans-media projects.
15. Light -- Core Rules -- Hard Light and Soft Light -- Lights and Lighting -- Lighting Quick-Reference Guide -- 16. Camera Movement -- Going Handheld -- Handheld Tracking -- Camera Pans and Tilts -- Dolly Shot -- Tripod Dolly -- 17. The Two-Page Film School -- 18. Post-Mortem: Making a Short Documentary about the 2016 Presidential Election -- Pre-Production -- Production -- Post-Production -- Aftermath -- 19. Post-Production Workflow -- Review your Footage -- (Re)Consider your Audience's Relationship to the Film -- Plan a Working-Structure for your Film -- Begin Creating a Rough Cut -- Step Back -- Critically Review and Reassess -- Post-Mortem -- Refine Your Rough Cut -- Step Back, Review Your Fine Cut and Reassess -- Reflections -- 20. The Three-Act Structure -- 21. The Protagonist -- Harmon's Story Embryo -- Casting the Audience as the Protagonist -- The On-Screen Protagonist - The Journey -- 22. Assembly -- Editing -- Colour-Grading -- Sound-Tracking -- 23. Editing Workflow in Adobe Premiere Pro -- Step One: How to Start a New Project -- Step Two: Get to Know the Premiere Workspace -- Step Three: Import Video and Audio Clips into your Project -- Step Four: Move Clips into your Timeline -- Step Five: Shorten a Clip -- Step Six: Moving Clips Around the Timeline -- Step Seven: Cutting Between Clips -- Step Eight: Remove Unwanted Sound-tracks -- Step Nine: Add a New Sound-track -- Step Ten: Add On-Screen Text -- Step Eleven: Saving Your Project -- Step Twelve: Exporting Your Project -- Step Thirteen (Optional): Colour-Grading Your Project -- 24. Distribution and Dissemination -- Theatrical Release -- Digital Streaming -- Freely Accessible Digital Streaming -- Bibliography -- Illustrations.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books